THE IMPLEMENTATION OF ANAGRAM GAME TO IMPROVE STUDENTS’ VOCABULARY MASTERY AT JUNIOR HIGH SCHOOL - Muhammad Khoerul Hadist; Mila Rosdiana (Prodi Pendidikan Bahasa Inggris, STKIP Muhammadiyah Bogor, 2021)
The objective of the research was to find out whether the implementation of anagram game can improve students’ vocabulary mastery at seventh-grade students of MTS Manbaul Ulum. This research used a quantitative method and cluster sampling technique. The sample of this research was two-class as experimental class and control class, each class consisting of 30 students. The instrument was test. The pre-test and the post-test were given to the experimental class and control class. In this research, the writer used the normality test, and T-test to calculate and analyze data. Based on the data, it was found that the mean pre-test score in the experimental class was 29,53 and in control class was 27,22. Meanwhile, the mean post-test score in the experimental class was 59,46 and in control class was 35,66. For the Normality test, the Chi-Square in experimental class has statistic x² = 4,5 and in control class has statistic x² = 4. While the reference from the Chi-Square table with = 0.05 (5%) and degrees of freedom = 5 is 11,07. It means that the x² table is higher than the x² statistic. The difference between the two tests pre-test and post-test was evaluated using t-test analysis to prove hypothesis, where the significance level was alpha (?) 5% (0.05). The t-statistic 8,416 and t-table 2,021. The t-statistic > t-table means that the alternative hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected. Therefore, the writer concluded that anagram game can improve students’ vocabulary mastery at seventh-grade of MTS Manbaul Ulum